The Effect of Variation in Light Spectra on the Growth of Chlorella Vulgaris and It is Ability to Decolorize RB5 - Ummah, Faizatul; Saefi, Muhammad; Wahyudi, Didik (Bionature, 2025)
Reactive Black 5 (RB5) is an azo dye widely used in the textile industry and improper processing of this dye can harmful to the aquatic environment, including limited light penetration and potential carcinogenic and mutagenic effects on aquatic organisms. Therefore, RB5 in waters needs to be handled seriously, one of which is through bioremediation efforts using Cholera vulgaris. Meanwhile, chlorella growth is highly dependent on various light spectrums. This study aimed to examine the effect of different light spectrums (red, blue, and white) on C. vulgaris cell density-based growth and its ability to decolorate RB5. A completely randomized design with three replications was applied using 30 mg/L RB5 solution, and was conducted for 12 days at laboratoty. Cell density was measured by a hemocytometer, and dye concentration was analyzed using a UV-Vis spectrophotometer. The results showed that blue light produced the highest algal growth, reaching 2.78 × 10⁷ cells/mL on the ninth day. Meanwhile, white light produced the greatest RB5 decolorization, reaching 80% reduction on the last day. These findings highlight the role of different light spectrums in optimizing algal cell density and dye removal efficiency.